Larva Development and Growth of Mangrove Crab, Scylla tranquebarica Crablet from Individual Selection for the Broodstock Candidate - Gunarto, Gunarto; Syafaat, M. N.; Herlinah, Herlinah (Aquacultura Indonesiana, 2019)
A part of S. tranquebarica crablet offspring produced from larvae  rearing often grows faster than the others. The research aimed to monitor larvae development and compared the growth between fast and slow growth  crablet offspring. Hatched larvae reared until crablet stage with production 4848 individual. 600 individual were weighted and measured carapace width. The data figured as a normal distribution curve. 700 ind. of fast growth crablet with carapace width 15.2+1.29 mm and body weight  0.55+0.15 g/ind. were selected. The others 700 individual  slow growth crablet, carapace width  8.88+3.11 mm and body  weight  0.14+0.08 g/individual were selected also. These crablet   stocked in four pond compartments  each size of 500 m2 (350 ind./500 m2).  Crablet growth was  monitored monthly. After five months cultured, the fast growth crablet attained 185.7+38.7 g/ind. and significantly different (P<0.05) with the slow growth crablet 156.94+15.30 g/ind. The first female mature gonadal stage with weight 205.2+0.3g and carapace width 116.7+0.7mm was obtained from the fast growth crablet group after fourth months cultured. That female mature gonadal was spawned after 27 days incubated in the hatchery. Fast growth crablet is concluded  more effective for the broodstock candidate in mud crab hatchery.